Uma análise dos sentidos da não-participação para os moradores de uma favela em São Paulo nos serviços prestados por organizações do terceiro setor - Castro, Letícia Oppido de (2009)
This study aimed to understand the meanings of non-participation for the residents of Paraisópolis, a slum located in the southern region of São Paulo, in services provided by non-governmental organizations engaged in this community. The relevance of the topic expands the implications at the collectivity, because of the social question, as well as within the individual ambitious, by bringing the subject involved in this process the suffering caused by social inequality. For this purpose, this study had as reference the Sociohistorical Psychology and, from it, the categories of meaning, popular participation and the dialectical process of exclusion/inclusion. Moreover, subsidies were sought for a critical analysis of the role of third sector in the country. Interviews were held with residents and representatives of organizations of the community, which were analyzed based on Vygotsky. In the analysis it were identified descriptive categories of the most objective aspects, which were submitted to analysis of the subtext, showing various forms of manifestation of social inequality and powerlessness regarding participation. It was identified that there is a complex web of meanings that are narrow to social inequality and that appears in the speeches of residents and representatives of entities of the third sector, inside the structure of organizations and daily lives of people